Developmental Trajectories of Executive and Verbal Processes in Children with Phenylketonuria. Issue 3 (3rd April 2018) - Hawks, Zoë W.; Strube, Michael J.; Johnson, Neco X.; Grange, Dorothy K.; White, Desirée A.
ABSTRACT: Phenylketonuria (PKU) is a hereditary disorder characterized by disrupted phenylalanine metabolism and cognitive impairment. However, the precise nature and developmental trajectory of this cognitive impairment remains unclear. The present study used a verbal fluency task to dissociate executive and verbal processes in children with PKU ( n  = 23; 7–18 years) and controls ( n  = 44; 7–19 years). Data were collected at three longitudinal timepoints over a three-year period, and the contributions of age, group, and their interaction to fluency performance were evaluated. Results indicated impairments in executive processes in children with PKU, which were exacerbated by declining metabolic control.